Assessing the main opportunities of integrated biorefining from agro-bioenergy co/by-products and agroindustrial residues into high-value added products associated to some emerging markets: A review. (May 2018) - De Corato, Ugo; De Bari, Isabella; Viola, Egidio; Pugliese, Massimo
Abstract: Market implementation of integrated biorefinery requires reliable and advanced processing units combined with eco-friendly and economically profitable production chains. Future developments of integrated biorefinery systems should include either crop cultivation with selected genotypes that maximize full chain performances either the increasing use of disposable or/and underused biomass. The aim of this paper was to review the main biorefining opportunities related to agro-bioenergy co-products and agroindustrial residues potentially available on the World (as biofuel co/by-products, agricultural residues, agricultural by-products and agro-wastes), paying a special attention to high-value added products associated to some emerging markets. The current status and future perspectives of conversion from agro-bioenergy residual biomass into high-value bio-based products by innovative biorefineries have been considered. After a brief recognition on the nature and origin of the main categories of organic residuals derived from the biofuel chains and agricultural, forestry, food processing and animal activities within definitions given by the European Union, this paper has firstly focused its choice on the high-value added products associated to some chemical basic-platforms (succinic acid, cellulose, glycerin, proteins, peptides, enzymes, etc.). A special attention has also been done to high-value added bio-based products and commodities related to sustainable and renewable farming systems (soil amendment, phytosanitary drug, plant biostimulant and biofertilizer) and bio-based industries in producing innovative biomaterials (bioplastic, lignin and alginate). Finally, this paper has addressed own concern on the perspectives of integrated biorefining from organic residuals drawing particular attention to the European and Italian contexts giving and discussing some new opportunities for big players and stakeholders.